Habit of elongate amphibole particles as a predictor of mesothelial carcinogenicity - Andrey A. Korchevskiy; Ann G. Wylie (Toxicology Reports)
Introduction: Amphiboles are a class of minerals that are abundantly present in the environment. Amphiboles may exist in several habits, with asbestiform particles behaving like typical amphibole asbestos and non-asbestiform (or massive) reported to be less biologically active. Materials and methods: The available dimensional information for 16 testing sets (8 asbestiform and 8 non-asbestiform types of tremolite) was combined. In addition, three validation sets (an asbestiform sample from Eastern New York and non-asbestiform samples from Quebec and Falls Village, Connecticut) were tested by Transmission Electron Microscopy (TEM) to determine dimensional distribution. Mathematical modeling was utilized to determine the classification method for amphiboles with various habits. Results: The decision boundary method was developed to distinguish asbestiform vs. non-asbestiform samples (with error rate of 0 % for single-sourced tremolite and 3 % for potentially mixed samples). All validation datasets were correctly classified. A new empirical dimensional coefficient of carcinogenicity (DCC) was proposed, with DCC = 1 - exp(-0.11 Surface Area /(1000width3 + 1)). For several mineral types (crocidolite, amosite, Libby amphiboles, anthophyllite, chrysotile, and erionite), it was demonstrated that mesothelioma potency factors can be predicted based on DCC and biosolubility with a high level of accuracy (R=0.98, R2=0.96, p < 0.006). It was demonstrated that modeled mesothelioma potency correlates with relative potency for pleural instillation in Wistar rats, and correlates inversely with membranolytic toxicity index HC50. Mesothelioma potency was demonstrated to be negligible in all non-asbestiform sets. Conclusions: The habit of amphibole particles is predictive of biological behavior that can be estimated from the dimensional data for the particles.